Effective management of polyethers through depolymerization to symmetric and unsymmetric glycol diesters using a proton-exchanged montmorillonite catalyst. Issue 11 (4th May 2017) - Maeno, Zen; Yamada, Shota; Mitsudome, Takato; Mizugaki, Tomoo; Jitsukawa, Koichiro
Abstract : An efficient and practical method for catalytic depolymerization of polyethers to glycol diesters was developed using proton-exchanged montmorillonite. Abstract : From the standpoint of green sustainable chemistry, it is very important to build a resource recycling system. Herein, an efficient and practical method for catalytic depolymerization of polyethers to glycol diesters was developed using proton-exchanged montmorillonite (H-mont). H-mont uniquely exhibited high catalytic activity for the depolymerization of polyethers with benzoic anhydride to symmetric glycol dibenzoates under mild reaction conditions. Various symmetric and unsymmetric glycol diesters were obtained from the reaction of diverse polyethers with carboxylic acid derivatives. The high catalytic efficiency for this depolymerization of H-mont is interpreted by its character, in which the montmorillonite layers act as an effective two-dimensional macroligand to form the intercalated complex with polyethers. Furthermore, a new protocol for the utilization of waste polyethers in water was developed based on the catalytic and adsorption abilities of H-mont.